High entropy alloy as catalyst for degradation of azo dye in Fenton process - Abu Hassan, Nur Hudawiyah; Fadil, Nor Akmal; Ibrahim, Nor Fadhilah; Jami, Mohammed Saedi; Nordin, Norhuda Hidayah (American Institute of Physics, 2022)
The degradation of azo dyes is a major concern as the industrial effluent can cause pollution to the environment as well as affecting the human health and the aquatic ecosystem negatively. The wastewater treatment process helps to remove any undesirable substances or contaminants before releasing it back to the environment. Fenton process is one of the methods used for wastewater treatment whereby iron catalyzed hydrogen peroxide to generate hydroxyl radical. Recently, high entropy alloys (HEAs) with equimolar alloys of five or more elements exhibit remarkable catalytic properties. The HEA with composition of FeCoNiAlBSi has been proposed as a promising catalyst material to enhance the performance of the Fenton process in degrading azo dyes due to highly active sites and unique atomic structure of the HEA. Herein, the study of solid FeCoNiAlBSi HEA as a catalyst particularly in the Fenton and electro-Fenton process is studied to provide superior efficiency in degradation of Methyl Orange (MO).